2021
DOI: 10.3389/fendo.2021.681266
|View full text |Cite
|
Sign up to set email alerts
|

The Complicated Effects of Extracellular Vesicles and Their Cargos on Embryo Implantation

Abstract: As a rate-limiting step in pregnancy, embryo implantation is highly dependent on intercellular communication. Extracellular vesicles (EVs) are newly identified to be important in the course of intercellular communication. EVs have been isolated from a wide variety of biofluids and tissues, including plasma, liver, uterine, semen, embryo, etc. The present and future use of EVs not only as biomarkers, but also as targeting drug delivery system, is promisingly pave the way for advanced comprehension of implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 126 publications
0
15
0
Order By: Relevance
“…Exosomes play an important role in intercellular communication and have been isolated from a wide variety of biofluids and tissues, including plasma, liver, uterine, semen, embryo, etc. [ 17 ]. The role of exosomes in intercellular communication comprises mediating the exchange of substances between cells, thereby changing the biological properties of the recipient cells [ 26 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes play an important role in intercellular communication and have been isolated from a wide variety of biofluids and tissues, including plasma, liver, uterine, semen, embryo, etc. [ 17 ]. The role of exosomes in intercellular communication comprises mediating the exchange of substances between cells, thereby changing the biological properties of the recipient cells [ 26 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes can act not only as biomarkers, but also as targeted drug-delivery systems, and thus hold promise for an advanced comprehension of reproductive diseases [ 17 ]. However, the precise mechanisms of action of exosomes in oocyte maturation have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are involved in the suitable interaction between the embryo and uterine endometrium required for successful embryo implantation during pregnancy [ 92 ]. Endometrial epithelium can release exosomes into the uterine cavity and transfer specific miRNAs to the blastocyst or endometrial epithelial cells to enhance embryo implantation [ 93 ]. Comparing the miRNAs of the exosomes and their producer cells demonstrated that 13 of the 227 miRNAs were specific for exosomes and promoted embryo implantation [ 94 ].…”
Section: The Roles Of Exosomes In Embryo Implantationmentioning
confidence: 99%
“…Oviduct is the place where occur oocyte transportation, fertilization, and initial embryo development. Oviductal extracellular vesicles (oEVs), as the main components of oviduct fluid, can orchestrate gamete/embryo-oviduct and embryomaternal interactions, hence supporting oocyte mature (in canine), embryonic development, and motility, capacitation, and fertilizing ability of sperm [14,15]. The contents of oEVs (mRNAs, miRNAs, and proteins) are dynamic at different stages of the estrous cycle, suggesting that cargos of oEVs are under hormonal control [16].…”
Section: Evs Derived From the Oviductmentioning
confidence: 99%